Proceedings of the 16th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Innovation in Educat 2018
DOI: 10.18687/laccei2018.1.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Medición continúa de flujo de CO2 en suelo en una parcela de bosque tropical en Isla Barro Colorado, Canal de Panamá.

Abstract: Developing countries are aimed to protect and expand their forests as a mitigation action to Climate Change. Tropical soils contain a 32% of the total amount of carbon stored in soils. With the incrementation of anthropogenic CO2 in the atmosphere, there is a necessity to understand soil CO2 complex interaction with abiotic and biotic factors and their interplay with soil CO2 production and transport, so a clear comprehension, could lead researchers of this subject to forecast with precise models,CO2 flux in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Furthermore, Cantú-Silva et al [46] reported that soil CO 2 fluxes are directly influenced by T soil , where microorganisms responsible for the decomposition of soil organic matter are involved. Nevertheless, Sugasti et al [47] point out that, although there is a positive correlation between CO 2 efflux and T soil , variations in this variable are not the only factor driving soil CO 2 fluxes; therefore, each particular forest depends on a balance of conditions such as soil moisture content, belowground biomass and microorganisms, which play an important role in CO 2 production and transport to the soil surface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cantú-Silva et al [46] reported that soil CO 2 fluxes are directly influenced by T soil , where microorganisms responsible for the decomposition of soil organic matter are involved. Nevertheless, Sugasti et al [47] point out that, although there is a positive correlation between CO 2 efflux and T soil , variations in this variable are not the only factor driving soil CO 2 fluxes; therefore, each particular forest depends on a balance of conditions such as soil moisture content, belowground biomass and microorganisms, which play an important role in CO 2 production and transport to the soil surface.…”
Section: Discussionmentioning
confidence: 99%